Assessment of DNA damage and DNA damage response and repair in dormancy-enriched leukemia cells - Aldosari, Sahar (2017)
Acute myeloid leukaemia (AML) is a heterogeneous myeloid malignancy characterized by clonal expansion of abnormal/immature hematopoietic precursor cells in the bone marrow. A side compartment in the BM niche consists of abnormal, quiescent cells, which are called dormant leukemic initiating cells (DLICs). Patients with AML tend to respond well to remission induction chemotherapy, but relapse is common because current therapies cannot completely eradicate leukemic cells. It is widely accepted that CD34+CD38− DLICs are more resistant to chemotherapy and that they contribute to drug resistance and relapse of AML to a greater extent than progenitor CD34+CD38+ cells. DLICs have been extensively characterised, but they remain a critical area of investigation for clinical research because of the low prevalence of DLICs and similarity to normal HSCs. A model of dormancy in vitro that shows most of the features of DLICs had previously been established in the Nottingham Haematology Group. This study used this model and aimed to investigate whether the response to DNA damage was different in dormancy-enriched cells compared to cycling leukemic cells following chemotherapy. The amount of DNA damage was assessed up to 24 hours pre- and post- drug treatment using the neutral Comet assay. Lower levels of damage were observed in dormancy-enriched cells following etoposide (ETO) treatment at 4 hours (p = 0.04), although this switched at the 24 hour time point where accumulated DNA double-stranded breaks (DSBs), in dormancy-enriched KG1a cells were associated with a higher percentage of viable cells. DNA damage response cascade markers in both dormancy-enriched and cycling cells showed phosphorylation by flow cytometry (phospho-H2AX139, pATM-S1981, H2AX142, and pChk-Thr68) in response to conventional AML chemotherapy. Significantly lower levels of cleaved PARP-Asp214 and active caspase 3 were observed in dormancy-enriched cells treated with ara-c (p = 0.0001) or ETO (p = 0.0001) at 24 hours, strongly indicating that survival responses are activated in dormancy-enriched cells. Induction of 53BP1 foci, the hallmark of non-homologous end joining (NHEJ) was observed following treatment with ara-c (p = 0.038) and ETO (p = 0.049) in dormancy-enriched cells, indicating the NHEJ repair pathway is the preferred mechanism for DSB repair. At the molecular level, BTG2 expression was involved in the DNA damage response. Significant induction of BTG2 was detected in cycling treated cells with ETO for 24 hours. In conclusion, this study provides evidence that phosphorylation of H2AX139 and H2AX142 is a key response marker that may explain the mechanism underlying the drug resistance of DLICs and induction of repair. Therefore, results of this study may help in devising novel treatment strategies for AML that target H2AX142 of DLICs to permanently eradicate all leukemic cells and improve overall survival.